(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: English: This article explores the symbiotic relationship between meaning analysis and dynamic equivalence in the realm of translation studies. By unraveling the intricacies of meaning and emphasizing the dynamic adaptation of texts, translators can bridge linguistic and cultural gaps with finesse. Through a nuanced examination of these concepts, readers will gain insight into the art of conveying meaning across languages while preserving the essence and impact of the original text.